Regulatory Challenges and Social Dynamics of Online Notary Practices: A Comparative Legal Study of Indonesia and Malaysia - Satrio Abdillah; Norhasliza Ghapa; Maheran Makhtar (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
This study examines the social challenges and technology adoption processes in online notarial practices in Indonesia and Malaysia during and after the COVID-19 pandemic. The study employed a qualitative approach, involving in-depth interviews and document analysis. The analysis tool used was NVivo 12 Plus for coding optimization. The novelty of this study lies in its cross-country comparative analysis, specifically examining the interrelationships between social dynamics, digitalization, and legal challenges in online notarial practices in Indonesia and Malaysia during and after the COVID-19 pandemic, a previously unstudied approach. The main findings of this study indicate that the transformation of notarial practices in Indonesia and Malaysia after the COVID-19 pandemic was significantly influenced by the interaction between social dynamics, digital literacy levels, and legal regulatory readiness. Indonesia faces challenges such as legal uncertainty, gaps in access to technology, and low trust in digital services. At the same time, Malaysia has demonstrated faster adaptation due to a clearer regulatory framework and greater acceptance of technology. Differences in legal systems (civil law and common law) also shape the flexibility with which online notarial practices can respond to digitalization, thereby affecting the validity, legitimacy, and sustainability of online notarial practices in both countries. The digital transformation of notarial practice demands greater legal certainty through clear, adaptable regulations to ensure the validity, security, and legitimacy of online notary services. Therefore, harmonizing cybernotary regulations and strengthening digital governance are necessary to ensure that technological innovation aligns with fundamental legal principles.